Natural Gas in Road Transportation - A Low-emission Bridging Technology? - Hanna Wang-Helmreich; Stefan Lochner (Institute of Energy Economics at the University of Cologne (EWI), 2011)
Greenhouse gas emission reductions are at the centre of national and international efforts to mitigate climate change. In road transportation, many politically incentivised measures focus on increasing the energy efficiency of established technologies, or promoting electric or hybrid vehicles. The abatement potential of the former approach is limited, electric mobility technologies are not yet market-ready. In a case study for Germany, this paper focuses on natural gas powered vehicles as a bridging technology towards low-emission road transportation. Scenario analyses with a low level of aggregation show that natural gas-based road transportation in Germany can accumulate up to 464 million tonnes of CO2-equivalent emission reductions until 2030 depending on the speed of the diffusion process. If similar policies were adopted EU-wide, the emission reduction potential could reach a maximum of about 2.5 billion tonnes of CO2-equivalent. A model-based analysis shows that the comparative cost advantage of natural gas relative to petrol and diesel per energy unit is not significantly reduced by the increased gas demand from natural gas vehicles. Capital costs for the transformation of the transport system to natural gas are therefore accompanied by lower fuel costs. Specific emission abatement costs of natural gas based mobility decline over time. After between 15 and 20 years, they are projected to be relatively low or even negative when a maximum rate of diffusion of natural gas vehicles is assumed.
Keywords: L92; O33; Q41; Q54; 330; Emission reduction potential; Road transportation; Natural gas vehicles; Abatement costs; Low emission mobility; Alternative fuels